Taking graph applications to production (O'Reilly Media, 2019)
"Over the past decade, Denise Gosnell (DataStax) has helped build some of the largest production applications of graph databases around the world. From those experiences, she's collected a set of common areas in which teams frequently misstep when getting started with graph technology. It also happens that those themes parallel the experience of playing one of her favorite games, SimCity 2000. Denise walks you through a few of these topics."--Resource description page